Obligation to Approve the Use of Forest Areas for Mining Business Actors Operating in Protected Forest Areas (Case Study of PT Nickel Indonesia) - Muhammad Adli Az Lubis (Publikasi Indonesia, 2024)
PT Nickel Indonesia, which is a mining company that has held a Contract of Work since 1968, part of its mining area is located in the Protected Forest Area area so it must carry out business activities by the provisions that have been regulated related to PPKH. This article will discuss the obligations of mining business actors who own PPKH operating in protected forest areas by taking a case example from PT Nickel Indonesia. In addition, this article will also explain the sanctions that will be received for PPKH permit holders if they neglect the obligations that have been set by the government in the applicable regulations. On the other hand, this article will also try to examine how mining facilities have been built but are in the buffer zone. It is further explained in this article that, PPKH functions as a government control with obligations that must be fulfilled by business actors who obtain it. Violation of these obligations can result in administrative and criminal sanctions. The sanctions that may be received if they violate these obligations are a warning for PT Nickel Indonesia to improve business governance that pays attention to the environment. PT Nikel Indonesia's supporting facilities that existed in the buffer area before the regulation took effect are expected to continue to be used by receiving special policies from the government to support nickel ore mining and processing activities in Indonesia and of course, PT Nikel Indonesia as a PPKH holder is committed to maintaining transparency and communication with all stakeholders regarding the use of supporting facilities that have been built before the enactment of the regulation new ones.